2022
DOI: 10.3390/metabo12010078
|View full text |Cite
|
Sign up to set email alerts
|

Improving Infant Hydrocephalus Outcomes in Uganda: A Longitudinal Prospective Study Protocol for Predicting Developmental Outcomes and Identifying Patients at Risk for Early Treatment Failure after ETV/CPC

Abstract: Infant hydrocephalus poses a severe global health burden; 80% of cases occur in the developing world where patients have limited access to neurosurgical care. Surgical treatment combining endoscopic third ventriculostomy and choroid plexus cauterization (ETV/CPC), first practiced at CURE Children’s Hospital of Uganda (CCHU), is as effective as standard ventriculoperitoneal shunt (VPS) placement while requiring fewer resources and less post-operative care. Although treatment focuses on controlling ventricle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A pilot study at the Cure Hospital in Uganda showed that a postoperative decrease in cerebral tissue optical scattering (measured by frequency-domain NIRS) was highly predictive of treatment failure in infants undergoing endoscopic third ventriculostomy combined with choroid plexus cauterization to treat post-infectious hydrocephalus. 376 Early detection of treatment failure is critical in LMIC because most patients do not have easy access to medical care once they leave the hospital. In a nutritional intervention study in Guinea Bissau, researchers found increases in ipsilateral CBF (measured with DCS) in children who had taken a new dietary supplement for 23 weeks compared to controls.…”
Section: Clinical Applications Of Optical Spectroscopy and Imagingmentioning
confidence: 99%
“…A pilot study at the Cure Hospital in Uganda showed that a postoperative decrease in cerebral tissue optical scattering (measured by frequency-domain NIRS) was highly predictive of treatment failure in infants undergoing endoscopic third ventriculostomy combined with choroid plexus cauterization to treat post-infectious hydrocephalus. 376 Early detection of treatment failure is critical in LMIC because most patients do not have easy access to medical care once they leave the hospital. In a nutritional intervention study in Guinea Bissau, researchers found increases in ipsilateral CBF (measured with DCS) in children who had taken a new dietary supplement for 23 weeks compared to controls.…”
Section: Clinical Applications Of Optical Spectroscopy and Imagingmentioning
confidence: 99%
“…The mechanism of these indexes in secondary hydrocephalus is not very clear [ 17 , 18 ]. This study compared the levels of CSF-Cl, CSF-GS, CSF-MALB, and CSF-ADA between the hemorrhagic hydrocephalus group (H-HCP group) and tumor hydrocephalus group (T-HCP group) from January 2018 to April 2022 to explore the value of these four indicators in the differential diagnosis of secondary hydrocephalus, so as to provide clinical data support for the diagnosis and treatment of secondary hydrocephalus [ 19 , 20 ]. The inflammatory reaction of hemorrhagic hydrocephalus was significantly greater than that of tumor hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic third ventriculostomy (ETV) has emerged as a pivotal technique in the management of obstructive hydrocephalus, offering an alternative to the traditional shunt placement (1,2). This procedure, which creates a bypass within the ventricular system to facilitate cerebrospinal fluid (CSF) flow, is underpinned by a growing body of evidence that underscores its utility across diverse patient populations (3). Despite its increasing application, the discourse surrounding ETV is multifaceted, encompassing both its commendable success rates and the complexities inherent to its implementation (4).…”
Section: Introductionmentioning
confidence: 99%